Up To Eleven: Limitation Periods for Recovery of Unlawful State Aid - Stępkowski, Łukasz (PRAWO i WIĘŹ, 2025)
This paper revisits the issue of limitation periods with regard to State aid measures that do not comply with the standstill obligation, particularly in the context of their recovery. In light of the adoption of Regulation No. 2015/1589 and the evolving case law of the CJEU, the issue of limitation periods has become more important for those affected. However, the effect of the evolving case law has been to create different limitation periods for the Commission and national courts. Given that there is no longer a single limitation period in the context of state aid, this paper attempts to review applicable scenarios for such limitation periods. The law is stated as it stood on 1 September 2024, with some later developments added.